Asuhan Keperawatan Pendidikan Kesehatan Gizi Seimbang Pada Ibu Bayi A Di Desa Sungai Asam - Romadaningsih, Tri Widya; Santi, Eka (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
Balanced nutrition is very synonymous with toddlers, because balanced nutrition in toddlers is very important in the growth process. Data from the Karang Intan Health Center 2 of 86 toddlers showed that the distribution of nutrition for toddlers was 1 toddler with poor nutrition, as many as 16 toddlers with malnutrition, as many as 62 toddlers with good nutrition and 7 toddlers with excess nutrition